Edukasi Pemilahan Sampah Melalui Program Bank Sampah di Desa Maron Wetan - M. Imam Sya Roni; Brilian Prilindaputra; Putri Yasmin Imarotul Mujaddidah; Nailur Rohmah; Ardita Fajria Mayanti; Elly Uzlifatul Jannah (Jurusan Kesehatan Lingkungan Poltekkes Kemenkes Padang, 2025)
Waste management remains a pressing challenge in Maron Wetan Village, Probolinggo Regency, East Java. The situation is exacerbated by the community’s low awareness of waste separation, limited supporting infrastructure, and the influx of waste from outside the area. To address these issues, the Community Service Program (KKN) Group 52 of UIN Sunan Ampel Surabaya applied the Participatory Action Research (PAR) approach, which emphasizes collaboration and active engagement of local residents as key actors rather than passive research subjects. The program commenced with the mapping of 13 neighborhood units (RT) and field data collection, followed by analysis using the Matrix Ranking technique to determine priority interventions based on urgency, efficiency, and impact. The analysis identified three main priorities: low awareness of the long-term environmental impacts of waste (score 9), habitual disposal of waste into rivers (score 8), and inadequate waste management facilities (score 6). In response, two primary interventions were developed: (1) the establishment of a waste bank as an economic incentive scheme, and (2) the installation of educational signboards titled “How Long Does Your Waste Take to Decompose?” to promote environmental consciousness. Positive community responses were particularly evident in RT 2, RT 6, and RT 9, where active participation was observed. These findings highlight that an educational–participatory approach can enhance environmental awareness and encourage behavioral change, although the long-term sustainability of the program remains contingent upon structural support from the village government.